ANALISIS NILAI-NILAI MOTIVASI BELAJAR DALAM FILM AJARI AKU ISLAM - Abdurrahim; Zakiyatul Aziziyah (Jurnal Penelitian Ilmiah INTAJ, 2023)
Student success in learning is influenced by several factors, one of which is motivation. Motivation is described as the driving force behind all activities. Learning is very important as a source of high knowledge through science, enabling humans to find solutions and solve problems in their lives. This film depicts a phenomenon that is happening, one of which is that there are many non-Muslims who want to study Islam because of a certain factor, while in the community there are many Muslims whose knowledge of Islam is still small. From this phenomenon, it is necessary to further study how to increase the values of learning motivation. This type of research is qualitative with content analysis method. Based on data analysis in the film Ajari Aku Islam, there are two values of learning motivation that adhere to Hamzah B Uno’s theory, namely intrinsic learning motivation that comes from within Kenny, where Kenny has an interest in something. study hard, and persistent to achieve his desires. While extrinsic motivation comes from the support of friends and giving gifts.